2018
DOI: 10.1007/s00018-018-2850-8
|View full text |Cite
|
Sign up to set email alerts
|

OSBP-related protein-2 (ORP2): a novel Akt effector that controls cellular energy metabolism

Abstract: ORP2 is a ubiquitously expressed OSBP-related protein previously implicated in endoplasmic reticulum (ER)-lipid droplet (LD) contacts, triacylglycerol (TG) metabolism, cholesterol transport, adrenocortical steroidogenesis, and actin-dependent cell dynamics. Here, we characterize the role of ORP2 in carbohydrate and lipid metabolism by employing ORP2-knockout (KO) hepatoma cells (HuH7) generated by CRISPR-Cas9 gene editing. The ORP2-KO and control HuH7 cells were subjected to RNA sequencing, analyses of Akt sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 55 publications
2
36
0
Order By: Relevance
“…These observations suggested that a major function of ORP2 could involve the ER-LD interfaces and the TG metabolic processes occurring therein. However, the study of Kentala et al [27] revealed that the loss of ORP2 did not reduce ER-LD contacts, but under basal culture conditions rather increased them. However, this work indicated that the dynamic expansion of the ER-LD MCSs upon fatty acid loading may be disturbed in the ORP2 KO cells.…”
Section: Tissue Expression Pattern and Subcellular Localization Of Orp2mentioning
confidence: 92%
See 3 more Smart Citations
“…These observations suggested that a major function of ORP2 could involve the ER-LD interfaces and the TG metabolic processes occurring therein. However, the study of Kentala et al [27] revealed that the loss of ORP2 did not reduce ER-LD contacts, but under basal culture conditions rather increased them. However, this work indicated that the dynamic expansion of the ER-LD MCSs upon fatty acid loading may be disturbed in the ORP2 KO cells.…”
Section: Tissue Expression Pattern and Subcellular Localization Of Orp2mentioning
confidence: 92%
“…Cell cortex localization of ORP2 was also observed in human umbilical vein endothelial cells (HUVECs) that seldom have large LDs. In these cells, the protein was frequently found co-localizing with the actin regulator cortactin in lamellipodia [27].…”
Section: Tissue Expression Pattern and Subcellular Localization Of Orp2mentioning
confidence: 99%
See 2 more Smart Citations
“…More interestingly, three ORP genes were upregulated upon incubation of the cells with oxLDL: ORP2, ORP9 and ORP11. ORP2 regulates the membrane contact between ER and lipid droplets, providing a plausible explanation for its up-regulation under oxLDL exposure [42][43][44][45]. ORP9 localizes at the Golgi/ER interface and regulates phosphatidylinositol-4-phosphate (PI4P) metabolism in Golgi membranes, competitively with ORP4S [46].…”
Section: Discussionmentioning
confidence: 99%